Living with Diabetes - Nancy J. Gal; Linda B. Bobroff (EDIS)
Diabetes is a disease that affects more than 26 million Americans. Although there is no cure for type 1 or type 2 diabetes, diabetes can be managed with the proper care. If you have diabetes, the best way to live well is to learn about the disease and work with your doctor to develop a healthy living plan that is right for you. This revised 4-page fact sheet was written by Nancy J. Gal and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, July 2012.